PLATO as it is: A legacy mission for Galactic archaeology. Issue 6 (24th August 2017) - Miglio, A.; Chiappini, C.; Mosser, B.; Davies, G. R.; Freeman, K.; Girardi, L.; Jofré, P.; Kawata, D.; Rendle, B. M.; Valentini, M.; Casagrande, L.; Chaplin, W. J.; et al.
Abstract : Deciphering the assembly history of the Milky Way is a formidable task, which becomes possible only if one can produce high‐resolution chrono‐chemo‐kinematical maps of the Galaxy. Data from large‐scale astrometric and spectroscopic surveys will soon provide us with a well‐defined view of the current chemo‐kinematical structure of the Milky Way, but it will only enable a blurred view on the temporal sequence that led to the present‐day Galaxy. As demonstrated by the (ongoing) exploitation of data from the pioneering photometric missions CoRoT, Kepler, and K2, asteroseismology provides the way forward: solar‐like oscillating giants are excellent evolutionary clocks thanks to the availability of seismic constraints on their mass and to the tight age–initial mass relation they adhere to. In this paper we identify five key outstanding questions relating to the formation and evolution of the Milky Way that will need precise and accurate ages for large samples of stars to be addressed, and we identify the requirements in terms of number of targets and the precision on the stellar properties that are needed to tackle such questions. By quantifying the asteroseismic yields expected from PLATO for red giant stars, we demonstrate that these requirements are within the capabilities of the current instrument design, provided that observations are sufficiently long to identify the evolutionary state and allow robust and precise determination of acoustic‐mode frequencies. This will allow us to harvest data of sufficient quality to reach a 10% precision in age. This is a fundamental prerequisite to then reach the more ambitious goal of a similar level of accuracy, which will be possible only if we have at hand a careful appraisal of systematic uncertainties on age deriving from our limited understanding of stellar physics, a goal that conveniently falls within the main aims of PLATO's core science. We therefore strongly endorse PLATO's current design and proposed observational strategy, and conclude that PLATO, as it is, will be a legacy mission for Galactic archaeology.